AGRICULTURAL BY-PRODUCTS AS TOTAL MIXED RATIONS FOR BUFFALOES - Ismail, Dahlan (Proceeding Buffalo International Conference, 2013)
Appropriate use of relatively inexpensive agricultural by-products (ABP) is of paramount importance for profitable buffalo production. Utilization of agro-waste as livestock feedstuffs is an important strategy that should be included in the agricultural development master plan of Southeast Asian countries. Objectives of this paper are to provide information on suitable ABP that can be utilized as total mixed rations (TMR) for intensive and semi-intensive buffalo production systems, to identify appropriate processing technology for efficient utilization and storage, and to evaluate buffaloes performance and meat quality fed on ABP based TMR. ABP are usually imbalance in its nutrient composition. Mixing of ABP is usually needed in order to balance up nutrients composition in the diets. Use of TMR is appropriate for intensive production systems. Least cost formulations are important in determining the feed cost and return to investment. Feeding cost is about 70% of production cost in intensive feeding management. Cost of ABP based TMR were affordable and feeding management for buffaloes in the feedlot is practical. The technology is suitable for smallholders and large scale commercial buffalo production. The quality of meat from swamp buffaloes was usually variable and questionable. This could be due to improper production systems and poor feeding practice (low quality and quantity of diets). Studies showed that ABP diets enhanced the formation of marbling in buffalo muscles and produced better carcass conformation than the grazing buffaloes. The meat of swamp buffalo fed on ABP diet was tenderer and showed lower cooking loss than the meat from pasture-fed animals. In conclusion, the quality of buffalo meat can be improved through planned feeding systems by using right combinations of ABP in the diets of the animals. This study showed that buffalo meat is not inferior to beef provided that buffaloes are raised under proper feeding and management systems.